Adjuvant IL-7 or IL-15 overcomes immunodominance and improves survival of the CD8(+) memory cell pool - Melchionda, Fraia (American Society for Clinical Investigation, 2005)
Current models of T cell memory implicate a critical role for IL-7 in the effector-to-memory transition, raising the possibility that IL-7 therapy might enhance vaccine responses. IL-7 has not been studied, to our knowledge, before now for adjuvant activity. We administered recombinant human IL-7 (rhIL-7) to mice during immunization against the male antigen HY and compared these results with those obtained from mice immunized with rhIL-2 and rhIL-15. Administration of rhIL-7 or rhIL-15, but not rhIL-2, increased effector cells directed against these dominant antigens and dramatically enhanced CD8(+) effectors to subdominant antigens. The mechanisms by which the cytokines augmented effector pool generation were multifactorial and included rhIL-7–mediated costimulation and rhIL-15–mediated augmentation of the proliferative burst. The contraction phase of the antigen-specific response was exaggerated in cytokine-treated mice; however, CD8(+) memory pools in rhIL-7– or rhIL-15–treated groups demonstrated superior long-term survival resulting in quantitative advantages that remained long after the cytokines were discontinued, as demonstrated by improved survival after challenge with an HY-expressing tumor undertaken several weeks after cytokine cessation. These results confirm the adjuvant activity of rhIL-15 and demonstrate that rhIL-7 also serves as a potent vaccine adjuvant that broadens immunity by augmenting responses to subdominant antigens and improving the survival of the CD8(+) T cell memory pool.